Hypotonia, Ataxia, Developmental Delay and Tooth Enamel Defect Syndrome (HADDTS) due to a Heterozygous de Novo Missense Variant in CTBP1 Identified via Whole Genome Sequencing - Silvia Beatriz Sanchez Marco; Pardington, Emily; Monaghan, Marie; Spaull, Robert; Fadilah, Ala; Kurian, Kathreena; Vijayakumar, Kayal; Smithson, Sarah; Majumdar, Anirban (Case reports in pediatrics, 2025)
We describe a three‐year‐old girl with an unusual c‐terminal binding protein 1 ( CTBP1 ) gene variant. She presented with features of hypotonia, ataxia, developmental delay and tooth enamel defect syndrome (HADDTS), following numerous chest infections, poor weight gain and delayed motor development during the early years. After many years of genetic testing where no diagnosis was found, whole genome sequencing (WGS) identified a missense variant in the CTBP1 gene (NM_001012614.1): c.991C > T p.(Arg331Trp). We present some of the brain MRI (cerebellar atrophy) and muscle biopsy features (central nuclei/cores) characteristic of this condition. The underlying mechanisms have not yet been elucidated. Although the clinical features make this condition recognisable, we are aware that in the small community of patients with this condition, the time to diagnosis may be exceptionally long. WGS has allowed us to accelerate this process. We are hopeful that earlier identification will bring better care for the affected children and allow the genetic implications to be discussed with their families.